Evaluation of neurovascular anatomical variations in maxillary anterior region in cone beam computed tomography images - Farida Abesi; Fateme Saeedi; Sina Haghanifar; Ehsan Moudi; Soraya Khafri (Babol University of Medical Sciences, 2017)
Introduction: Incisive foramen in the maxilla is the oral terminus of the nasopalatine canal. This region is important in implantology, Therefore, the aim of this study was to investigate the  neurovascular anatomical variations in the maxillary anterior region, observed on cone beam computed tomography (CBCT) images. Materials &Methods: In this cross-sectional study, maxillary CBCT images from 200 patients (100 men, 100 women, average age 45.61±11.01) were evaluated in sagittal, axial and coronal sections and the following parameters were investigated: incisive canal diameter, shapes of canal, presence of accessory canal in the anterior palate and their location, thickness of  buccal bone in the sections containing canal, patient's dental and periodontal status in terms of bone loss. Data were collected and analyzed using SPSS, V20. P≤0.05 was considered significant. Results: In sagittal view, the mean diameter of the canal was 2.36±0.69mm.Age and gender did not significantly influence the diameter. Morphological analysis of canal showed that 25% of them were hourglass-like,23.5% conical,22%funnel,27.5% cylindrical, 2% tree branch. Accessory canals were observed in 58 patients (29%) specially near to the canine region. The thickness of  buccal bone plate was less in complete edentulous patients than others and also there was a significant relationship between bone loss and canal size in the hourglass and cylindrical shapes. Conclusion: In this study, the prevalence of accessory canals was relatively significant, so it seems essential to carry out cone beam computed tomography in this area for determining the canal morphology and dimensions before implant placement.